2017
DOI: 10.1097/cej.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

The association between coffee consumption and bladder cancer incidence in a pooled analysis of the Miyagi Cohort Study and Ohsaki Cohort Study

Abstract: Recent epidemiological studies of the association between coffee consumption and the risk of bladder cancer have yielded conflicting results. The aim of the present study was to examine the association between coffee consumption and the incidence of bladder cancer on the basis of pooled data from two cohort studies carried out in Miyagi Prefecture, northeastern Japan. We delivered self-administered questionnaires inquiring about the frequency of coffee consumption and other lifestyle factors in 1990 for the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…It could, therefore, be suggested that the increased BC risk is due to the caffeine content of coffee. Previous epidemiological studies already confirmed this hypothesis by showing a null association between BC risk and decaffeinated coffee [71] and an increased BC risk for caffeinated coffee [72,73]. The present study also showed an increased BC risk when comparing caffeinated coffee consumers versus decaffeinated coffee consumers.…”
Section: Discussionsupporting
confidence: 88%
“…It could, therefore, be suggested that the increased BC risk is due to the caffeine content of coffee. Previous epidemiological studies already confirmed this hypothesis by showing a null association between BC risk and decaffeinated coffee [71] and an increased BC risk for caffeinated coffee [72,73]. The present study also showed an increased BC risk when comparing caffeinated coffee consumers versus decaffeinated coffee consumers.…”
Section: Discussionsupporting
confidence: 88%
“…However, this positive association was restricted to ever smokers, particularly current smokers, and we observed no evidence of an association among never smokers. Previous prospective cohort studies, conducted in the United States, Europe, and Asia, with smoking-adjusted analyses have provided little evidence for a positive, independent, dose-response relationship between coffee drinking and risk of bladder cancer, 1724 and two studies observed inverse associations among adults in Japan 25 and women in the Netherlands. 26 Nevertheless, positive associations in case-control studies, 27 which are difficult to interpret due to potential recall and selection bias, as well as suggestive, but imprecise positive trends in some cohort studies 20, 22, 24, 26 have sustained speculation that coffee drinking causes bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the few cohort studies that have conducted sensitivity analyses among never smokers have had very limited case numbers in this subgroup, and risk estimates have been imprecise and inconsistent. 20, 25, 26 …”
Section: Discussionmentioning
confidence: 99%
“…We carried out a pooled analysis of two prospective cohort studies, the Miyagi Cohort Study and the Ohsaki Cohort Study, details of which have been described previously elsewhere. [9][10][11] In brief, for the Miyagi Cohort Study, we distributed a self-administered questionnaire to all 51,921 subjects (26,642 women and 25,279 men) aged 40-64 years resident in 14 municipalities of Miyagi Prefecture, northeastern Japan, between June and August 1990. We collected eligible questionnaires from 24,769 47,605 of those subjects (response rate: 91.7%).…”
Section: Study Populationmentioning
confidence: 99%